Conceptualizing Critical Education and Anthropological Assessment to Expand the Scale of Higher Design Education in India - Chahal, Navneet Kaur (Journal of Research in Vocational Education, 2024)
The study explores the challenges and gaps in design education in India, highlighting the lack of a specialized category for design subjects in the UGCNET examination list. It underscores the importance of granting an autonomous identity to design education, separate from visual arts, to better reflect the fields distinct nature. Drawing from personal experiences and academic interactions, the author identifies significant issues such as inadequate illustrative resources and the need for a comprehensive curriculum in design. The paper also addresses broader concerns in India’s higher education system, including bias and corruption in PhD admissions, calling for reforms to ensure transparency and meritocracy. The aim is to enhance the stature and effectiveness of design education and integrate it more fully into India’s academic framework. The article advocates for a paradigm shift in design education, characterized by a holistic and inclusive approach that transcends institutional boundaries and fosters a culture of innovation and excellence. By addressing the structural deficiencies and systemic biases, the paper endeavours to pave the way for a more equitable and reputable educational framework that resonates with India's global aspirations.